Penanaman Nilai Akhlakul Karimah Melalui Film Kartun Riko The Series di Kelas VII MTs Nurul Huda Sukaraja - Amelia, Olpa; Marlina, Marlina (JUPIN (Jurnal Pendidikan Islam Nusantara), 2022)
Inculcating the values ​​of moral education is very important for society regardless of age limit, especially in children. In this millennial era, educational media is not only obtained from print media, educational media in the form of electronics can also provide moral or moral education. The aims of this study are: To determine the moral values ​​contained in the animated film Riko the Series. To find out the cultivation of moral values ​​contained in the cartoon film Riko The Series. To find out the supporting and inhibiting factors in inculcating moral values ​​through the cartoon film Riko The Series. The results of the study show that friendship is an attitude or action that pays attention to the pleasure of talking, associating and collaborating with others, a supporting factor in inculcating moral values ​​through the cartoon film Riko the Series in class VII MTs Nurul Huda Sukaraja, namely the existence of IMTAQ (Faith and Faith) activities. Taqwa) is held every Friday.